Restrição externa, dependência estrutural de commodities primárias e o investimento direto externo no Brasil - Nascimento, Erica Patente (2011)
As the beginning of the discussion about the reprimarization process of the Brazilian exportations, or about a deindustrialization process of the country foreign sales, this study purpose that the discussion, actually, should be about the existence of the commodities structural dependence as a way to face the foreign restrictions. Therefore the intention is to show that, historically, the way that the Brazilian economy has crossed for its development depends of the foreign capital, mainly in its way of Foreign Direct Investment (FDI), and in the balance generated by the primary products, which make us try to understand the impact of this capital for the equilibrium of the Brazilian Payment Balance and also for the economy. These points were discussed not only based on the Brazilian classic writers as Francisco Oliveira, Caio Prado Jr. and Celso Furtado, but also using the newest studies which contributes to point the causes and consequences of the external capital dependence in the actual scenario. The conclusions acquired in the end of the study, indicates the fact that the Brazilian specialization in products of low aggregated value is not recent. Brazil is, historically, a competitive country in primary products. At the same time, the country importation always was a pressure factor of the National Payments Balance, being composed by products with more aggregated value. According to some authors, this characteristic of the Brazilian Economy will be surpassed with the economic opening process, which will attract external capital making possible the modernization of the Brazilian productive sector. Therefore, we can claim that the FDI, in the way it has been inserted in the country, does not offer the opportunity to get out of the commodities dependence, as generators of the payment balances, because the country international competitive standard didn t get any important changes, keeping itself out of the step related to the global standard which has been intensified in products with more aggregated value. The changes in the national insertion standard directed to more technological products is really important to surpass the historical scenario of commodities dependence, making the country less vulnerable to external crisis.